2014
DOI: 10.1186/1471-2164-15-25
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs and their target genes in developing maize ears by combined small RNA and degradome sequencing

Abstract: BackgroundIn plants, microRNAs (miRNAs) are endogenous ~22 nt RNAs that play important regulatory roles in many aspects of plant biology, including metabolism, hormone response, epigenetic control of transposable elements, and stress response. Extensive studies of miRNAs have been performed in model plants such as rice and Arabidopsis thaliana. In maize, most miRNAs and their target genes were analyzed and identified by clearly different treatments, such as response to low nitrate, salt and drought stress. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 69 publications
(118 reference statements)
8
78
0
Order By: Relevance
“…The length of the sRNAs ranged from 18 to 25 nt, and in both the IFC and CFC libraries, the 24 nt category was most abundant (average of 51.07%; Figure 2A). This is consistent with the typical lengths of plant sRNAs reported in other studies (Liu et al, 2014; Hackenberg et al, 2015). Of the known miRNAs, 21-nt miRNAs were most abundant (59.7%) (Figure 2B), representing the dominant size of mature miRNAs in plants.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The length of the sRNAs ranged from 18 to 25 nt, and in both the IFC and CFC libraries, the 24 nt category was most abundant (average of 51.07%; Figure 2A). This is consistent with the typical lengths of plant sRNAs reported in other studies (Liu et al, 2014; Hackenberg et al, 2015). Of the known miRNAs, 21-nt miRNAs were most abundant (59.7%) (Figure 2B), representing the dominant size of mature miRNAs in plants.…”
Section: Resultssupporting
confidence: 93%
“…Recent studies have reported the role of miRNAs in determining gene expression during maize ear and kernel development (Liu et al, 2014; Xin et al, 2015). However, few studies have examined miRNA expression during ovary growth, in particular, during carpel fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital gene expression libraries were generated using a NEBNext Ultra RNA Library Prep Kit for Illumina (New England Biosystems), following the manufacturer's recommendations. Small RNA libraries were prepared as described previously (Liu et al, 2014a).…”
Section: Rna Isolation and Sequencing Library Constructionmentioning
confidence: 99%
“…Many known miRNAs and their targets are conserved across different plant species (Montes et al, 2014). In maize, many conserved miRNA targets have been experimentally confirmed (Shen et al, 2013;Zhai et al, 2013;Zhao et al, 2013;Liu et al, 2014), but a few exceptions exist, for example those of miR168 and miR399. MiRNAs are members of multiple regulatory networks controlling plant development, and many miRNA families also play roles in stress responses and tolerance (for review, see Sunkar et al, 2012).…”
mentioning
confidence: 99%